MHD characteristics of compression zone in plasma stream generated by MPC - Chebotarev, V.V.; Cherednychenko, T.N.; Eliseev, D.V.; Garkusha, I.E.; Kozlov, A.N.; Kulik, N.V.; Ladygina, M.S.; Marchenko, A.K.; Morgal, Ya.I.; Petrov, Yu.V.; Solyakov, D.G.; Staltsov, V.V. (Вопросы атомной науки и техники, 2012)
An investigation of local MHD plasma parameters in flow and characterizations of plasma streams, generated by different types of plasma accelerators and magneto-plasma compressors, is one of actual and important from point of view basic plasma dynamics research and plasma applications in different technologies. The present paper devoted to analysis of magneto-hydrodynamic characteristics of the plasma stream generated by the MPC compact geometry. Such important parameters as spatial distributions of electric current and spatial distribution of electromagnetic force in plasma stream, plasma density and velocity in compression zone have been investigated.